Genome-Wide Association Study for Biomass Related Traits in a Panel of Sorghum bicolor and S. bicolor × S. halepense Populations - Habyarimana, Ephrem; De Franceschi, Paolo; Ercisli, Sezai; Baloch, Faheem Shehzad; Dall’Agata, Michela (Frontiers in Plant Science, 2020)
The efficient use of sorghum as a renewable energy source requires high biomass yields and reduced agricultural inputs. Hybridization of Sorghum bicolor with wild S. halepense can help meet both requirements, generating high-yielding and environment friendly perennial sorghum cultivars. Selection efficiency, however, needs to be improved to exploit the genetic potential of the derived recombinant lines and remove weedy and other wild traits. In this work, we present the results from a Genome-Wide Association Study conducted on a diversity panel made up of Sorghum bicolor and an advanced population derived from S. bicolor x S. halepense multi-parent crosses. The objective was to identify genetic loci controlling biomass yield and biomass-relevant traits for breeding purposes. Plants were phenotyped during four consecutive years for dry biomass yield, dry mass fraction of fresh material, plant height and plant maturity. A genotyping-by-sequencing approach was implemented to obtain 92,383 high quality SNP markers used in this work. Significant marker-trait associations were uncovered across eight of the ten sorghum chromosomes, with two main hotspots near the end of chromosomes 7 and 9, in proximity of dwarfing genes Dw1 and Dw3. No significant marker was found on chromosomes 2 and 4. A large number of significant marker loci associated with biomass yield and biomass-relevant traits showed minor effects on respective plant characteristics, with the exception of seven loci on chromosomes 3, 8, and 9 that explained 5.2 – 7.8% of phenotypic variability in dry mass yield, dry mass fraction of fresh material, and maturity, and a major effect (R^2= 16.2%) locus on chromosome 1 for dry mass fraction of fresh material which co-localized with a zinc-finger homeodomain protein possibly involved in the expression of the D (Dry stalk) locus. These markers and marker haplotypes identified in this work are expected to boost marker-assisted selection in sorghum breeding.